2021
DOI: 10.1051/0004-6361/202140551
|View full text |Cite
|
Sign up to set email alerts
|

The New Generation Planetary Population Synthesis (NGPPS)

Abstract: Context. State-of-the-art planet formation models are now capable of accounting for the full spectrum of known planet types. This comes at the cost of an increasing complexity of the models, which calls into question whether established links between their initial conditions and the calculated planetary observables are preserved. Aims. In this paper, we take a data-driven approach to investigate the relations between clusters of synthetic planets with similar properties and their formation history. Methods. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 140 publications
(161 reference statements)
2
23
0
Order By: Relevance
“…Sabotta et al 2021;Cloutier et al 2021). Moreover, combinations of terrestrial planets and sub-Neptunes are also commonly predicted by population synthesis models based on the core accretion paradigm of planet formation (Emsenhuber et al 2021;Schlecker et al 2021;Burn et al 2021). Following the angular momentum deficit stability criterium from Laskar & Petit (2017), the system would be stable for eccentricities of the outer companion candidate up to 0.45.…”
Section: Implications For a Multi-planet Systemmentioning
confidence: 96%
“…Sabotta et al 2021;Cloutier et al 2021). Moreover, combinations of terrestrial planets and sub-Neptunes are also commonly predicted by population synthesis models based on the core accretion paradigm of planet formation (Emsenhuber et al 2021;Schlecker et al 2021;Burn et al 2021). Following the angular momentum deficit stability criterium from Laskar & Petit (2017), the system would be stable for eccentricities of the outer companion candidate up to 0.45.…”
Section: Implications For a Multi-planet Systemmentioning
confidence: 96%
“…Sabotta et al 2021;Cloutier et al 2021). Moreover, combinations of terrestrial planets and sub-Neptunes are also commonly predicted by population synthesis models based on the core accretion paradigm of planet formation (Emsenhuber et al 2021;Schlecker et al 2021;Burn et al 2021). Following the angular momentum deficit stability criterium from Laskar & Petit (2017), the system would be stable for eccentricities of the outer companion candidate up to 0.45.…”
Section: Implications For a Multi-planet Systemmentioning
confidence: 98%
“…Accounting for the effects of N-body interactions when trying to invert planet formation thus seems challenging. Interestingly, it has recently been shown that while N-body interactions tend to randomize the process of planet formation, machine-learning techniques such as random forests still allow us to predict the outcome of planet formation quite accurately (Schlecker et al 2021). In this work the authors show that the initial parameters of the planet formation model described in , mainly the initial location of the planetary embryo and the dust mass of the disk, may be used to predict which class a forming planet will belong to (super-Earths, Neptune-like, giant planets, etc.).…”
Section: Planet Formationmentioning
confidence: 99%
“…The distribution of bulk planetary properties such as mass, radius, and orbital parameters encodes critical information that constrains planet formation models (see, e.g., Ida & Lin 2004;Alibert et al 2005;Mordasini et al 2009;Hasegawa & Pudritz 2011;Lambrechts & Johansen 2012;Bitsch et al 2015;Nayakshin & Fletcher 2015;Cridland et al 2016;Schlecker et al 2021). In addition, the chemical composition of planet atmospheres has long been regarded as a key to unlocking the process of planet formation (e.g., Gautier & Owen 1989;Owen & Encrenaz 2003) and is the explicit goal of many atmospheric characterization studies (see, e.g., Madhusudhan 2019, for a recent review).…”
Section: Introductionmentioning
confidence: 99%